Past experience of women during childbirth in the periphery of western mountain region of Nepal during childbirth - Shah, Rajiv; Baral, Gehanath; Basnyat, Subi; Shrestha, Sharmila (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To explore the past experience of women during childbirth in terms of respectful maternity on institutional deliveries in the region. Methods: This is a cross sectional descriptive study among women during outdoor visit at Karnali Academy of Health Sciences in Jumla from April to August 2020. Data were analyzed in terms of seven components of respectful maternity care. Results: The prevalence of obstetrics mistreatment was 78.5%. From 200 respondents, more than half had hospital delivery and one-fourth at local birthing center. Two-third of them perceives the care provided to them was proper and 85% opt to visit again to the same center in next pregnancy. Around 70-80% by ethnic group and at least three-fourth by the site of delivery have experienced at least one type of mistreatment. Conclusions: Indicators of respectful maternity care are not satisfactory in the western mountainous region. Keywords: institutional delivery, mistreatment, respectful maternity care